Obstructive sleep apnea and vitamin D level : Has the dust settled? - Loh, Huai Heng; Norlela, Sukor (John Wiley & Sons Ltd., 2023)
Obstructive sleep apnea and vitamin D deficiency are associated with multiple complications with increased morbidity and mortality. However, the relationship between these two entities remains unclear, with clinical studies demonstrating contradictory results. This narrative review aims to present the current evidence and understanding of this relationship and discuss the possible mechanisms linking these two disease entities. Finally, we summarize and propose areas of opportunity for future research.